2004
DOI: 10.13031/2013.17624
|View full text |Cite
|
Sign up to set email alerts
|

Stream Flow Estimation Using Spatially Distributed Rainfall in the Trinity River Basin, Texas

Abstract: Rainfall is the driving force behind all hydrologic processes in a watershed, and therefore the driving force in hydrologic modeling. In the past, raingauge data has been used as the primary input for these models. However, raingauge networks are generally sparse and insufficient to capture the spatial variability across large watersheds. A relatively new alternative is high−resolution radar rainfall data from weather radar systems, such as the Next Generation Weather Radar (NEXRAD) of the National Weather Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 12 publications
(14 reference statements)
1
33
0
Order By: Relevance
“…After an accurate analysis of the dry period, which included rainfall and measured and simulated streamflow, it was evident that the low performance was mainly due to few flood events occurred in 2010 due to convective rainfalls. In these cases, to enhance SWAT simulation results, Moon, Srinivasan, and Jacobs () and Kalin and Hantush () suggest to use Next‐Generation Weather Radar precipitation. Unfortunately, in the Carapelle watershed, these kind of data were not available.…”
Section: Resultsmentioning
confidence: 99%
“…After an accurate analysis of the dry period, which included rainfall and measured and simulated streamflow, it was evident that the low performance was mainly due to few flood events occurred in 2010 due to convective rainfalls. In these cases, to enhance SWAT simulation results, Moon, Srinivasan, and Jacobs () and Kalin and Hantush () suggest to use Next‐Generation Weather Radar precipitation. Unfortunately, in the Carapelle watershed, these kind of data were not available.…”
Section: Resultsmentioning
confidence: 99%
“…However, Hernandez et al (2000) found that increasing the number of simulated rain gauges from 1 to 10 resulted in clear estimated streamflow improvements (Table 2). Moon et al (2004) found that SWAT's streamflow efficiency improved (Table 2) when Next Generation Weather Radar (NEXRAD) precipitation input was used instead of rain gauge inputs. Jayakrishnan et al (2005) also found that NEXRAD precipitation input resulted in improved streamflow estimates relative to rain gauge data (Table 2).…”
Section: Climate Data Resolution Effectsmentioning
confidence: 99%
“…lag time) of 5 min rather than 1 min gives more reliable correlograms for the stratiform event (Figure 8). Thus, 5-min resolution data may be acceptable for fully distributed rainfall-runoff modelling of the 4 km 2 Sapat Kalisun catchment during stratiform events, but 1-min resolution data may be needed for convective events (see Moon et al (2004) and Smith et al (2004)). …”
Section: Local Spatial Variation In Rain-event Duration and Intensitymentioning
confidence: 99%